Risk factors of intraoperative oxygen desaturation: A case-control study of 152,314 anesthetics - Somrat Charuluxananan (2018)
Background: The present study was part of the Thai Anesthesia Incidents Study (THAI Study) of anesthetic adverse outcomes. Objective: To determine factors related to intraoperative oxygen desaturation (SpO 2 ≤ 85% or < 90% for more than 3 min) Material and Method: During a 12-month period (February 1, 2003 - January 31, 2004), a prospective multicentered registry of patients receiving anesthesia was conducted in 20 hospitals across Thailand. Anesthesia personnel filled up patient-related, surgical-related, and anesthesia related variables and adverse outcomes including intraoperative oxygen desaturation. A case-control (1:4) study of patients with and without intraoperative oxygen desaturation in the THAI Study database was done. Univariate and multivariate analysis were used to identify factors related to intraoperative oxygen desaturation. A p-value < 0.05 was considered as significant. Results: Among 152,314 patients without preanesthetic desaturation in the database, 328 cases of intraoperative oxygen desaturation were matched with 1,312 control patients without desaturation. Variables that predict desaturation by multiple logistic regression were age less than 5 years old [OR 9.3 (95% CI 5.4-16.0)], ASA physical status 3, 4, 5 [OR 3.1 (95% CI 2.2-4.3)], history of upper respiratory tract infection [OR 10 (95% CI 1.9-51.6)], history of asthma [OR 2.9 (95% CI 1.0-9.5)], general anesthesia [OR 4.0 (95% CI 2.4-6.7)] duration of anesthesia 31-90 min [OR 1.9 (95% CI 1.2-3.0)], duration of anesthesia 91-150 min (OR 2.2 (95% CI 1.3-3.6)], and duration of anesthesia > 150 min [OR 2.0 (95% CI 1.2-3.4)]. Conclusion: Knowing the risk factors of intraoperative oxygen desaturation helps improving personnel to improve preanesthetic conditions and facilitate early detection as well as prompt treatment of intraoperative oxygen desaturation.